Incidence and Outcome of Childhood Acute Leukemia in A Tertiary Care Hospital of Bangladesh Armed Forces - Nahar, Kamrun; Ferdousi, Shormin Ara; Hasan, Ahmed Rashidul; Islam, Afiqul; Islam, Azizul (Dhaka Shishu (Children) Hospital Journal, 2023)
Background: Worldwide cancer is the second leading cause of death in children under 15 years and acute leukemia is the most prevalent cancer among children. Objective: The objective of the study was to analyze the incidence and overall outcome of childhood leukemia patients aged 0-12 years in Combined Military Hospital (CMH), Dhaka. Methods: It was a retrospective cross-sectional study. Children below 12 years of age with confirmed diagnosis of leukemia and received treatment from the paediatric oncology unit of department of paediatrics of CMH, Dhaka were taken for this study. Data has been collected from Hospital based cancer registry records from 2011 to 2021. There present status has been collected from regular OPD or by phone calls. Results: The commonest cancer was found Acute Leukemia (52%), among them Acute Lymphoblastic Leukemia (ALL) 83.15% and Acute Myeloid Leukemia (AML) 16.85%. Morphological (FAB classification) sub-divisions revealed ALL-L2 (31%) was the commonest group for ALL. In case of AML, AML-M3 (APML) was the commonest (27%). Immunophenotyping of cells revealed Pre-B ALL was the commonest. Cytogenetic analysis revealed ETV6-RUNX1 (21%), t(1;19) ((q23,p13) E2A/PBX1 (11%) were two most common genetic abnormalities found in ALL and t(15;17) (q22;q12) M3,M3v PML-RARA was the commonest cytogenetic abnormalities and (8;21) (q22;q22) RUNX1/RUNX1T1 for AML. In case of ALL overall survival was 54% and in case of AML 40%. About 10% of patients reported relapses. Conclusion: Incidence of acute leukemia was the highest among all childhood cancer. At the end of the study, overall survival was 52% of cases, and relapses were seen in 10% of cases. DS (Child) H J 2021; 38(1): 17-26